A Cat-Bite Wound Infected With Vibrio Alginolyticus Following Use Of Sea Cucumber Oil - Mohamed, NA; Joseph, PG; Hussin, H; Hashim, R (Southeast Asian Ministers Educ Organization, 2024)
Indexed by WOS/SCOPUS